2013
DOI: 10.1016/j.ydbio.2012.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of Shh levels by Kras and Fgfr2 during hair follicle development

Abstract: Activating mutations in the KRAS oncogene are associated with three related human syndromes, which vary in hair and skin phenotypes depending on the involved allele. How variations in RAS signals are interpreted during hair and skin development is unknown. In this study, we investigated the developmental and transcriptional response of skin and hair to changes in RAS activity, using mouse genetic models and microarray analysis. While activation of Kras (KrasG12D) in the skin had strong effects on hair growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 67 publications
6
22
0
Order By: Relevance
“…Although activation by NF-kappaB is maintained, SHH is repressed by FGF signaling, mediated by placodal FGFR2 (Fig. 2B, center) [40,53]. Dermal Shh signaling is influenced by PTCH1, and PTCH1 upregulation is achieved by GLIs as described previously, together with Runx2 [31,54].…”
Section: Eda Pathway Until This Point In Hf Development Wnt Andsupporting
confidence: 51%
“…Although activation by NF-kappaB is maintained, SHH is repressed by FGF signaling, mediated by placodal FGFR2 (Fig. 2B, center) [40,53]. Dermal Shh signaling is influenced by PTCH1, and PTCH1 upregulation is achieved by GLIs as described previously, together with Runx2 [31,54].…”
Section: Eda Pathway Until This Point In Hf Development Wnt Andsupporting
confidence: 51%
“…These data suggest that Sox4 may negatively regulate Ihhb at least in part through the activation of Bmp7b. We also analyzed the expression of four additional regulators of Hh signaling: two Hh inhibitors ( fgfr2 and kras ), and two Hh activators ( lhx8 and nkx6.1 ; (Cai et al, 2000; Flandin et al, 2011; Mukhopadhyay et al, 2013). Fgfr2 was downregulated in sox4 morphant heads at 18 hpf and lhx8 was upregulated in sox4 morphants at 12 hpf, suggesting that these genes may also function downstream of Sox4 and upstream of Hh signaling during eye development (Figure S5, Student's t -test, P<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and murine models have demonstrated that cyclical on/off switching of the RAS pathway is required for the onset of catagen, hair cycle progression and maintenance of hair follicles . In a murine model with activated Kras, this lead to the development of hair loss, disorderly oriented hair follicles and wavy coat and curly whiskers . Abnormal anagen hairs were common in both CFCS and CS, suggesting abnormal hair cycling.…”
Section: Discussionmentioning
confidence: 99%
“…3 In a murine model with activated Kras, this lead to the development of hair loss, disorderly oriented hair follicles and wavy coat and curly whiskers. 3,[22][23][24] Abnormal anagen hairs were common in both CFCS and CS, suggesting abnormal hair cycling. One clinical example of abnormal hair cycling is loose anagen, where hairs typically demonstrate a deformed anagen bulb, an absent inner root sheath and a ruffled cuticle accompanied with a complete absence of telogen hairs.…”
Section: Discussionmentioning
confidence: 99%